Polyester polyol, polyester polyurethane, adhesive and laminate using the same
The development of a specific polyester polyester polyol copolymer addresses the challenge of creating biodegradable adhesives with excellent adhesion, meeting market requirements and ensuring environmental sustainability.
Patent Information
- Application Number
- JP2021072305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-04-22
Smart Images

Figure 0007666096000001 
Figure 0007666096000002 
Figure 0007666096000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester polyol, a polyester polyurethane, and an adhesive and a laminate using the same. [Background technology]
[0002] In recent years, in order to meet the increasing demand for plastics, mass production of plastics has been unavoidable, but at the same time, mass consumption and mass disposal have become social problems. Incinerated or landfilled plastics are a cause of global warming and soil and marine pollution. Biodegradable resins that take these problems into consideration have been developed, and demonstration tests are being conducted at companies, universities, and other research institutes. Furthermore, biomass, a biological resource other than fossil resources, is attracting attention as a non-exhaustible industrial resource. In particular, plants grow by absorbing carbon dioxide (CO2) from the atmosphere through photosynthesis using sunlight as energy. Therefore, products made from plant-derived raw materials (biomass plastics, synthetic fibers, etc.) are thought to have no effect on the increase or decrease of CO2 in the atmosphere (carbon neutral) because the amount of CO2 absorbed by photosynthesis during the plant's growth process is offset by the amount of CO2 emitted by the incineration of the plant (carbon neutral), and their development is expected.
[0003] In response to this growing environmental awareness, plastic products made from petrochemicals, which have been considered to have a large impact on the ecosystem, are being replaced by plastic products made from biodegradable resins, especially in the field of consumer goods. Biodegradable resins have a smaller molecular weight due to resin decomposition, particularly hydrolysis, caused by the effects of ultraviolet light and moisture, and some of the resins with a smaller molecular weight are decomposed into water and carbon dioxide by the action of microbial enzymes. However, in the field of consumer goods, durability, especially hydrolysis resistance, is required until the time of actual consumption, and plastic products made from biodegradable resins are required to have moderate durability and biodegradability.
[0004] In the field of food packaging and cosmetic pouches for consumer goods, various packaging materials have a multi-layer structure to express their functions. Although packaging materials and the food trays contained therein have been replaced with biodegradable plastic products, the adhesives used to bond each layer are conventional petrochemical-derived substances, and biodegradability has not yet been imparted to the packaging materials and pouches as a whole. A representative biodegradable resin is polylactic acid, which is made from plant-derived lactic acid. However, polylactic acid has a high glass transition temperature and poor flexibility, so the productivity when manufacturing laminates and its adhesion to sheet-like substrates are insufficient.
[0005] Patent Document 1 describes a specific polyol, a polyisocyanate compound having an isocyanate group at the end, and an average particle size of 1×10 -4 and a powder having a particle size of 0.2 mm or more.
[0006] Patent Document 2 discloses a lactic acid-based polyester laminate paper consisting of paper and a lactic acid-based polyester having a weight average molecular weight of 20,000 to 400,000 and a melting point of 70°C to 200°C by DSC, the weight average molecular weight including a structural unit obtained by dehydration condensation of lactic acid and a polyester structural unit obtained by dehydration condensation of dicarboxylic acid and diol. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2011-162579 A [Patent Document 2] Japanese Patent Application Publication No. 08-300570 Summary of the Invention [Problem to be solved by the invention]
[0008] However, the current situation is that these adhesives are unable to simultaneously achieve both biodegradability and adhesiveness that meet the standards required by the market in recent years. [Means for solving the problem]
[0009] As a result of extensive research into the above-mentioned problems, the present inventors have found that the problems can be solved by using the polyester polyol described below, and have arrived at the present invention.
[0010] The present invention relates to the following inventions [1] to
[11] .
[0011] [1] A polyester polyol having a number average molecular weight of 300 to 3,000 and being a polymer of polyester polyol (AB), lactide (C) and a cyclic monomer (D) (excluding lactide (C)), which is obtained by polymerizing the above, and the polyester polyol (AB) is a reaction product of a hydroxyl group component (A) containing a diol (a) having a branched structure, and a carboxylic acid component (B) containing an aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms.
[0012] [2] The polyester polyol according to [1], wherein the cyclic monomer (D) contains caprolactone.
[0013] [3] The polyester polyol according to [1] or [2], wherein the diol (a) having a branched structure is selected from the group consisting of 1,2-propylene glycol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,3-butanediol, 2,4-diethyl-1,5-pentanediol, and 2-ethyl-1,3-hexanediol.
[0014] [4] The polyester polyol according to any one of [1] to [3], wherein the content of the diol component (a) having a branched structure is 15 to 100 mol % in 100 mol % of the hydroxyl group component (A).
[0015] [5] The polyester polyol according to any one of [1] to [4], wherein the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms includes at least one selected from the group consisting of succinic acid, sebacic acid, and azelaic acid.
[0016] [6] The polyester polyol according to any one of [1] to [5], wherein the content of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms is 30 to 100 mol % in 100 mol % of the carboxylic acid component (B).
[0017] [7] A polyester polyurethane (X) having an isocyanate group, which is a reaction product of the polyester polyol according to any one of [1] to [6] above and a polyisocyanate (E).
[0018] [8] An adhesive comprising the polyester polyol according to any one of [1] to [6].
[0019] [9] An adhesive comprising the polyester polyurethane (X) having an isocyanate group described in [7].
[0020]
[10] A laminate comprising an adhesive layer formed from the adhesive according to [8] or [9] on a sheet-like substrate.
[0021]
[11] The laminate according to
[10] , wherein the sheet-like substrate is a biodegradable substrate. Effect of the Invention
[0022] The present invention makes it possible to provide polyester polyols and polyester polyurethanes that are capable of expressing biodegradability that meets the standards required by the market and have good handling properties (fluidity), as well as laminate adhesives and laminates that use the same and have excellent adhesive properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The following describes in detail an embodiment of the present invention. However, the description of the components described below is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.
[0024] In this specification, any numerical range specified using "to" is intended to include the numerical values before and after "to" as the lower and upper limit values of the range. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types. The number average molecular weight in this specification is a value measured using a GPC (gel permeation chromatography) "HPL-8420GPC" manufactured by Toso, and the viscosity is a value measured using a cone plate viscometer (CV-S1 manufactured by Toa Kogyo Co., Ltd.) Details are described in the Examples section.
[0025] The polyester polyol of the present invention may be referred to as polyester polyol (ABCD) in this specification. The polyester polyol (ABCD) does not include polyester polyol (X).
[0026] Polyester polyol (ABCD) The polyester polyol (ABCD) of the present invention is a copolymer of a polyester polyol (AB) having a number average molecular weight of 300 to 3,000, a lactide (C), and a cyclic monomer (D) (excluding lactide (C)). The polyester polyol (AB) is a reaction product of a hydroxyl group component (A) containing a diol (a) having a branched structure, and a carboxylic acid component (B) containing an aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms.
[0027] The polyester polyol (ABCD) of the present invention can be made into an adhesive composition capable of forming a laminate having excellent biodegradability and adhesiveness by mixing the polyester polyol (ABCD) with a crosslinking agent. From the viewpoint of handling properties in the step of mixing with the crosslinking agent, the polyester polyol (ABCD) of the present invention preferably has flowability. That is, the polyester polyol (ABCD) of the present invention preferably has fluidity at 60°C. The viscosity of the polyester polyol (ABCD) at 60°C is preferably 1,000 to 20,000 mPa·s, more preferably 1,000 to 10,000 mPa·s, and even more preferably 1,000 to 5,000 mPa·s. When the viscosity range of the polyester polyol (ABCD) at 60°C is 1,000 to 20,000 mPa·s, an adhesive composition having appropriate fluidity and being uniformly mixed with the crosslinking agent can be obtained, and a uniform adhesive layer can be formed on the sheet-like substrate.
[0028] <Polyester polyol (AB)> The polyester polyol (AB) is a reaction product of a hydroxyl group component (A) containing a diol (a) having a branched structure and a carboxylic acid component (B) containing an aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms, except for the polyester polyol (ABCD). The number average molecular weight of the polyester polyol (AB) is 300 to 3,000, and preferably 400 to 2,500. When the number average molecular weight of the polyester polyol (AB) is 300 to 3,000, the affinity to the substrate is increased, and the adhesiveness is improved.
[0029] [Hydroxyl group component (A)] The hydroxyl group component (A) contains a diol (a) having a branched structure. By having a branched structure, it is possible to introduce a branched structure into the resulting polyester polyol (AB) and lower the glass transition temperature. As a result, the glass transition temperature of the polyester polyol (ABCD) of the present invention is lowered, and the flowability is improved, resulting in good adhesion to the substrate.
[0030] (Diol (a) with branched structure) Examples of the diol (a) having a branched structure include 1,2-propylene glycol, dipropylene glycol, polyoxypropylene glycol, 1,2-butylene glycol, 1,3-butylene diol, 2-butyl-2-ethyl-1,3-propane diol, neopentyl glycol, dineopentyl glycol, 3-methyl-1,5-pentane diol, 2,4-diethyl-1,5-pentane diol, 3,3'-dimethylol heptane, 2-ethyl-1,3-hexane diol, polyether diol, polycarbonate diol, polyolefin diol, acrylic diol, and polyurethane diol. Among these, it is preferable from the viewpoint of biodegradability to contain at least one of 1,2-propylene glycol, 3-methyl-1,5-pentanediol, 1,3-butanediol, 2,4-diethyl-1,5-pentanediol, 2-ethyl-1,3-hexanediol, 2-butyl-2-ethyl-1,3-propanediol, and neopentyl glycol. Furthermore, 1,2-propylene glycol and neopentyl glycol are preferable because they are plant-derived raw materials and therefore can increase not only biodegradability but also the degree of biomass.
[0031] (Other hydroxyl components) Furthermore, for the hydroxyl group component (A), polyols having a branched structure other than the diol component (a) can be used within the scope that does not impair the effects of the present invention. Examples of such polyols include ethylene glycol, diethylene glycol, polyoxyethylene glycol, 1,3-propylene glycol, butylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,9-nonanediol, trimethylolpropane, glycerin, pentaerythritol, sorbitol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, and the like. Among these, ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol are preferred as diols in terms of biodegradability, and 1,3-propylene glycol and 1,4-butanediol are more preferred because they are easily available and are derived from plants, which makes it possible to increase the biomass degree of the resulting polyester.As polyols with three or more hydroxyl groups, glycerin, pentaerythritol, and sorbitol are preferred because they are derived from plants and can increase the biomass degree of the resulting polyester.
[0032] The content of the diol component (a) having a branched structure is preferably 15 to 100 mol %, more preferably 15 to 85 mol %, and particularly preferably 30 to 70 mol %, in 100 mol % of the hydroxyl group component (A). When the content of the diol component (a) having a branched structure is within the above-mentioned range, the flowability of the polyester polyol (AB) portion in the polyester polyol (ABCD) of the present invention is obtained, the handleability in the production of the adhesive composition is improved, and furthermore, the biodegradability can be increased.
[0033] [Carboxylic acid component (B)] The carboxylic acid component (B) contains an aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms. By containing the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms, the polyester component (AB) which is a reaction product with the hydroxyl group component (A) has appropriate biodegradability and can obtain sufficient adhesiveness.
[0034] (Aliphatic dicarboxylic acids having 2 to 12 carbon atoms (b)) Examples include dibasic acids such as adipic acid, azelaic acid, sebacic acid, succinic acid, fumaric acid, glutaric acid, tetrahydrophthalic acid, hexahydrophthalic acid, maleic acid, itaconic acid, etc., or their anhydrides, dialkyl esters, etc. Among these, succinic acid, sebacic acid, and azelaic acid are preferred in terms of biodegradability, and among these, succinic acid and sebacic acid are more preferred because they are not only easily available but also are derived from plants, making it possible to increase the biomass degree.
[0035] (Other carboxylic acid components) In addition, the carboxylic acid component (B) may contain a carboxylic acid other than the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms, as long as the effects of the present invention are not impaired. Examples of such a carboxylic acid include terephthalic acid, isophthalic acid, 2,5-furandicarboxylic acid, naphthalenedicarboxylic acid, long-chain fatty diacids, and trimellitic acid.
[0036] The content of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms is preferably 30 to 100 mol % in 100 mol % of the carboxylic acid component (B). By including an appropriate amount of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms, good biodegradability is obtained and sufficient adhesiveness is also obtained. The higher the content of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms, the more preferable, and the lower limit of the content of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms is more preferably 30 mol % or more, and even more preferably 40 mol % or more. This is because by making it 30 mol % or more, both biodegradability and adhesive strength are improved.
[0037] [Production method of polyester polyol (AB)] The polyester polyol (AB) is produced by reacting a hydroxyl group component (A) with a carboxylic acid component (B). In the production of the polyester polyol (AB) of the present invention, a known reaction accelerator can be used. Examples of the reaction accelerator include metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dimaleate, and tin 2-ethylhexanoate; tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diaza-bicyclo(4,3,0)nonene-5, and 6-dibutylamino-1,8-diaza-bicyclo(5,4,0)undecene-7; and reactive tertiary amines such as triethanolamine. Organic titanium compounds Specific examples of the titanium compounds include tetraalkoxy titanium compounds such as tetraisopropyl titanate, tetra-n-butyl titanate, tetra-2-ethylhexyl titanate, and tetrastearyl titanate; titanium acylate compounds such as polyhydroxytitanium stearate; and titanium chelate compounds such as titanium acetylacetonate, triethanolamine titanate, titanium ammonium lactate, titanium ethyl lactate, and titanium octylene glycol. Examples of the aluminum compounds include aluminum acetylacetonate and aluminum acetate.
[0038] The reaction accelerator is preferably inactivated with a deactivator after the reaction is completed, which is advantageous in preventing a decrease in the molecular weight of polylactic acid. As such a deactivator, for example, a phosphorus-based compound is preferably used. For example, organic ligands consisting of a group of chelating ligands having an imino group and capable of coordinating to a polymerization metal catalyst, and low oxidation number phosphoric acids having an acid value of 5 or less, such as dihydridooxophosphoric acid (I), dihydridotetraoxodiphosphoric acid (II, II), hydridotrioxophosphoric acid (III), dihydridopentaoxodiphosphoric acid (III), hydridopentaoxodi(II, IV), dodecaoxohexaphosphoric acid (III), hydridooctaoxotriphosphoric acid (III, IV, IV), octaoxotriphosphoric acid (IV, III, IV), hydridohexaoxodiphosphoric acid (III, V), hexaoxodiphosphoric acid (IV), decaoxotetraphosphoric acid (IV), hendecaoxotetraphosphoric acid (IV), and eneoxotriphosphoric acid (V, IV, IV), have the formula Examples include orthophosphoric acid, represented by the formula xH2O.yP2O5, where x / y = 3; polyphosphoric acid, where 2>x / y>1, and which are called diphosphoric acid, triphosphoric acid, tetraphosphoric acid, pentaphosphoric acid, etc. depending on the degree of condensation, and mixtures of these; metaphosphoric acid, represented by the formula x / y = 1, especially trimetaphosphoric acid and tetrametaphosphoric acid, and ultraphosphoric acid, represented by the formula 1>x / y>0, which has a network structure in which part of the phosphorus pentoxide structure remains (these are sometimes collectively referred to as metaphosphoric acid compounds), as well as acid salts of these acids, partial esters of monovalent and polyvalent alcohols or polyalkylene glycols, complete esters, phosphites, and phosphono-substituted lower aliphatic carboxylic acid derivatives.
[0039] When obtaining the polyester polyol (AB), an organic solvent may be included to adjust the viscosity of the resin in the system to an appropriate level. Examples of the organic solvent include ketone compounds such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester compounds such as methyl acetate, ethyl acetate, butyl acetate, ethyl lactate, and methoxyethyl acetate; ether compounds such as diethyl ether and ethylene glycol dimethyl ether; aromatic compounds such as toluene and xylene; aliphatic compounds such as pentane and hexane; and halogenated hydrocarbon compounds such as methylene chloride, chlorobenzene, and chloroform. These solvents may be used alone or in combination of two or more.
[0040] The polyester polyol (AB) preferably has fluidity at 60° C. and a viscosity of preferably 50 to 10,000 mPa·s, more preferably 300 to 4,000 mPa·s. By setting the viscosity range of the polyester polyol (AB) to 50 to 10,000 mPa·s, the polyester polyol (AB) can be easily handled in the next step of polymerizing the polyester polyol (AB), lactide (C), and cyclic monomer (D).
[0041] From the viewpoint of biodegradability, the polyester polyol (AB) has an acid value of preferably from 0 to 10 (mgKOH / g), more preferably from 0 to 5 (mgKOH / g). If the acid value is higher than 10 (mgKOH / g), the polyester polyol (AB) becomes susceptible to hydrolysis, and the durability required in the field of consumer goods cannot be obtained.
[0042] The polyester polyol (AB) preferably has a higher biomass degree, preferably 10 to 100% (%), more preferably 20 to 100% and particularly preferably 30 to 100%.
[0043] <Lactide (C)> Lactide (C) is a cyclic compound having two ester bonds in a molecule formed by dehydration condensation of the hydroxyl group and the carboxyl group of two molecules of hydroxy acid, and examples thereof include glycolide, 3,6-dimethyl-1,4-dioxane-2,5-dione (derived from 2-hydroxypropionic acid (lactic acid)), and 1,6-dioxacyclodecane-2,7-dione (derived from 4-hydroxybutanoic acid). Among these, the so-called lactides derived from lactic acid may be optically active substances, and include L-lactide, D-lactide, and meso-lactide. Among these, L-lactide and meso-lactide are preferred because they are not only easily available, but also derived from plants, and therefore can increase not only biodegradability but also biomass degree.
[0044] Such polyesters having a lactic acid skeleton are decomposed by enzymes secreted from microorganisms in soil, and therefore can be made to have a small impact on the environment.
[0045] The lactide (C) preferably contains meso-lactide. By containing an appropriate amount of meso-lactide, the glass transition temperature of the polyester polyol (ABCD) is lowered, the flowability of the polyester polyol (ABCD) is improved, and it is possible to ensure the mixability with the crosslinking agent and the adhesive strength during the production of the adhesive composition. The content of meso-lactide is preferably from 40 mol % to 100 mol %, and more preferably from 50 mol % to 100 mol %, in 100 mol % of lactide (C).
[0046] <Cyclic Monomer (D)> The cyclic monomer (D) is a monomer such as a cyclic lactone, a cyclic lactam, or a cyclic ether, except for lactide (C). By polymerizing lactide (C) and cyclic monomer (D), the glass transition temperature of the resulting polyester polyol (ABCD) is lowered, making it possible to ensure good mixability with a crosslinking agent and adhesive strength during adhesive production.
[0047] Examples of cyclic lactones include ε-caprolactone, δ-valerolactone, and γ-nonalactone. Examples of cyclic lactams include β-lactam, γ-lactam, and δ-lactam. Examples of cyclic ethers include ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, and dioxane. Among these, ε-caprolactone is preferred in terms of biodegradability.
[0048] It is preferable that ε-caprolactone is contained in an amount of 10 to 100 mol % based on 100 mol % of the cyclic monomer (D). By containing an appropriate amount of ε-caprolactone, the polyester has good fluidity at 60° C., and can have excellent handleability. The higher the proportion of ε-caprolactone, the more preferable. The lower limit of the proportion of ε-caprolactone is more preferably 40 mol % or more, and even more preferably 50 mol % or more.
[0049] <Production method of polyester polyol (ABCD)> The polyester polyol (ABCD) may be produced by any method as long as it contains polyester polyol (AB), lactide (C) and cyclic monomer (D), but a method of reacting lactide (C) and cyclic monomer (D) at the terminal hydroxyl group of polyester polyol (AB) is simple and preferable. Furthermore, it is preferable to include a step of reducing pressure in the production method in order to distill off unreacted lactide (C) and cyclic monomer (D). The glass transition temperature can be controlled by the weight ratio of the lactide component (C) / cyclic monomer component (D). The weight ratio of the lactide component (C) / cyclic monomer component (D), C / D, is preferably 0.05 to 19, more preferably 0.2 to 10, and particularly preferably 0.5 to 3. The molecular weight of the polyester polyol (ABCD) of the present invention can be controlled by the weight ratio AB / CD. The weight ratio AB / CD is preferably 0.05 to 1, more preferably 0.2 to 0.8.
[0050] The reaction catalyst, reaction terminator, and reaction solvent may be the same as those used in the production method of the polyester polyol (AB).
[0051] The polyester polyol (ABCD) of the present invention preferably has a number average molecular weight (Mn) of 1,000 to 20,000, more preferably 2,000 to 10,000, from the viewpoints of adhesive strength and fluidity. When the number average molecular weight (Mn) is 1,000 or more, adhesive strength can be exhibited, and when it is 20,000 or less, fluidity at 60° C. is improved, which is preferable. Here, the polyester polyol (ABCD) of the present invention is a polyester polyol containing the polyester polyol (AB), lactide (C) and cyclic monomer (D). Therefore, the number average molecular weight of the polyester polyol (ABCD) of the present invention is always larger than the number average molecular weight of the polyester polyol (AB), and the two do not overlap.
[0052] From the viewpoints of adhesive strength and fluidity, the polyester polyol (ABCD) preferably has a glass transition temperature (Tg) of -70°C to 0°C, more preferably -60°C to -15°C. When the polyester polyol (ABCD) has a glass transition temperature (Tg) in the range of -70°C to 0°C, the fluidity is good, and the mixability with the crosslinking agent during the production of the adhesive composition is improved. Furthermore, the affinity to the substrate is increased when the adhesive composition is attached to a sheet-like substrate, and the adhesive strength after aging is also improved.
[0053] As described above, the polyester polyol (ABCD) preferably has fluidity at 60°C, and the viscosity of the polyester polyol (ABCD) at 60°C is preferably 1,000 to 20,000 mPa·s, more preferably 1,000 to 10,000 mPa·s. It is even more preferably 1,000 to 5,000 mPa·s. By setting the viscosity range of the polyester polyol (ABCD) at 60°C to 1,000 to 20,000 mPa·s, it is possible to obtain an adhesive composition that has appropriate fluidity and is uniformly mixed with the crosslinking agent, and also to form a uniform adhesive layer on the sheet-like substrate.
[0054] The polyester polyol (ABCD) preferably has a higher biomass degree, preferably 10 to 100% (%), more preferably 20 to 100% and particularly preferably 30 to 100%.
[0055] From the viewpoint of solving environmental problems, the biodegradability of the polyester polyol (ABCD) is preferably as high as possible. It is preferably 20 to 100%. It is more preferably 40 to 100%. It is particularly preferably 60 to 100%. The higher the biodegradability, the greater the proportion of the material that is ultimately decomposed into water and carbon dioxide, which is more environmentally friendly.
[0056] Polyester polyurethane having isocyanate groups (X) The polyester polyurethane (X) having an isocyanate group of the present invention is a reaction product of a polyester polyol (ABCD) obtained by polymerizing a polyester polyol (AB) having a number average molecular weight of 300 to 3,000, a lactide (C), and a cyclic monomer (D) (excluding lactide (C)), and a polyisocyanate (E). The polyester polyol (AB) is a reaction product of a hydroxyl group component (A) containing a diol (a) having a branched structure, and a carboxylic acid component (B) containing an aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms.
[0057] <Polyisocyanate (E)> The polyisocyanate (E) can be selected from conventionally known polyisocyanates. The polyisocyanate (E) may be any of aliphatic, araliphatic, and aromatic polyisocyanates, and may also be a known diisocyanate or a compound derived from a diisocyanate.
[0058] Examples of the aliphatic polyisocyanate include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, 2,6-diisocyanate methyl caproate, and 1,5-pentamethylene diisocyanate; 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatome diisocyanate, and the like. alicyclic diisocyanates such as methyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatemethyl)cyclohexane, 1,3-bis(isocyanatemethyl)cyclohexane, etc.; or polyisocyanates such as allophanate type, nurate type, biuret type, adduct type derivatives derived from the above-mentioned aliphatic diisocyanates or alicyclic diisocyanates, or complexes thereof.
[0059] Examples of aromatic aliphatic isocyanates include 1,3- or 1,4-xylylene diisocyanate or mixtures thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or mixtures thereof, Examples of the aromatic diisocyanate include toluene diisocyanate, diphenylmethane diisocyanate, and the like. Polyisocyanates derived from 1,5-pentamethylene diisocyanate or hexamethylene diisocyanate are preferred because they have low crystallinity and good handleability. 1,5-pentamethylene diisocyanate is particularly preferred because it is partially derived from plants and can increase the biomass content of the resulting polyester polyurethane.
[0060] <Method for producing polyester polyurethane (X) having isocyanate group> The polyester polyurethane of the present invention may be produced by any method as long as it has a constituent unit of the polyester polyol (ABCD) of the present invention and a constituent unit derived from the polyisocyanate (E). However, a production method in which a terminal hydroxyl group of the polyester polyol (ABCD) is reacted with an isocyanate group of the polyisocyanate (E) is simple and preferable. In order to obtain a polyester polyurethane (X) having an isocyanate group at its terminal, the ratio of the number of isocyanate groups in the polyisocyanate (E) to the number of hydroxyl groups in the polyester polyol (ABCD) is appropriately selected, but in order to obtain a polyester polyurethane (X) having an isocyanate group, it is necessary to make the isocyanate groups derived from the polyisocyanate (E) in excess of the hydroxyl groups derived from the polyester polyol (ABCD). The ratio of the number of isocyanate groups / the number of hydroxyl groups is preferably 1 to 6, and more preferably 1.2 to 4. By being in the range of 1 to 6, a polyester polyurethane (X) having an isocyanate group at its terminal with excellent adhesiveness can be obtained.
[0061] Adhesive Composition The adhesive composition is a composition containing at least one of the polyester polyol (ABCD) of the present invention and the polyester polyurethane (X) having an isocyanate group, and other components may be used in combination.
[0062] The other components may be blended with the polyester polyol (ABCD) or with the polyester polyurethane (X) having an isocyanate group.
[0063] Examples of other components include organic solvents, crosslinking agents, polyols, and optional components.
[0064] When the polyester polyol (ABCD) and the polyester polyurethane (X) having an isocyanate group are liquid at 60°C, they can be used as a solventless adhesive. In addition, in order to improve the leveling property, they may be diluted with an organic solvent before use. As the organic solvent, for example, esters such as ethyl acetate, ketones such as methyl ethyl ketone, aromatic hydrocarbons such as toluene and xylene, etc. are preferably used, and can be appropriately selected and used.
[0065] <Examples of adhesive compositions containing polyester polyol (ABCD)> In the case of the adhesive composition containing the polyester polyol (ABCD) of the present invention, the composition may contain the polyester polyol (ABCD) and, if necessary, a crosslinking agent. The crosslinking agent is a compound for reacting polymers with each other and chemically changing them. By including the crosslinking agent, the polyester polyols (ABCD) are reacted with each other and chemically changed. For example, the above-mentioned polyisocyanate (E) may be blended with the polyester polyol (ABCD) as a crosslinking agent to form a two-component curing urethane adhesive. The weight ratio of the isocyanate groups of the polyisocyanate to the hydroxyl groups in the polyester polyol (ABCD) is appropriately selected, but they are preferably blended so that the polyester polyol (ABCD) / polyisocyanate (E) is 100 / 80 to 100 / 3, and more preferably 100 / 40 to 100 / 5.
[0066] Example 1 of an adhesive composition containing polyester polyurethane (X) having an isocyanate group In the case of the adhesive composition containing the polyester polyurethane (X) having an isocyanate group of the present invention, a crosslinking agent may be included as necessary. By including a crosslinking agent, the polyester polyurethane (X) having an isocyanate group is reacted with itself to chemically change it. Examples of the crosslinking agent include diols, triols, polyols, etc. containing a hydroxyl group component. Specifically, 1,2-propylene glycol, dipropylene glycol, polyoxypropylene glycol, 1,2-butylene glycol, 1,3-butylene diol, 2-butyl-2-ethyl-1,3-propane diol, neopentyl glycol, dineopentyl glycol, 3-methyl-1,5-pentane diol, 2,4-diethyl-1,5-pentane diol, 3,3′-dimethylol heptane, 2-ethyl-1,3-hexane diol Diols such as ethylene glycol, diethylene glycol, polyoxyethylene glycol, 1,3-propylene glycol, butylene glycol, 1,6-hexanediol, 1,4-butanediol, and 1,9-nonanediol; Triols such as trimethylolpropane and glycerin, By blending pentaerythritol, sorbitol, polytetramethylene ether glycol, polyester polyol (excluding the polyester polyol (AB) and polyester polyol (ABCD) of the present invention), polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, the polyester polyol (AB) and polyester polyol (ABCD) of the present invention, etc., a two-component curing type urethane adhesive can be made. The weight ratio of the hydroxyl-terminated crosslinking agent to the terminal isocyanate groups of the polyester polyurethane (X) having an isocyanate group is appropriately selected, but is preferably blended so that the polyester polyurethane (X) having an isocyanate group / hydroxyl-terminated crosslinking agent is 100 / 80 to 100 / 3, more preferably 100 / 40 to 100 / 5. When the crosslinking agent is not included, a part of the terminal isocyanate groups of the polyester polyurethane (X) having an isocyanate group is converted to an amine by moisture in the air, and crosslinked by reacting with the moisture and the unreacted isocyanate groups to become an adhesive.
[0067] Example 2 of an adhesive composition containing polyester polyurethane (X) having an isocyanate group Furthermore, the adhesive composition may contain a polyester polyurethane (X) having an isocyanate group as a crosslinking agent. For example, a two-component curing urethane adhesive may be prepared by blending a polyester polyurethane (X) having an isocyanate group as a crosslinking agent with a polyester polyol (excluding the polyester polyol (AB) and polyester polyol (ABCD) of the present invention), a polycarbonate polyol, a polyolefin polyol, an acrylic polyol, a polyurethane polyol, the polyester polyol (AB) of the present invention, or the polyester polyol (ABCD). The weight ratio of the isocyanate groups of the polyester polyurethane (X) having an isocyanate group to the hydroxyl groups in the polyol component is appropriately selected, but is preferably polyol component / polyester polyurethane (X) having an isocyanate group=100 / 80 to 100 / 3, more preferably 100 / 40 to 100 / 5.
[0068] <Other polyols> The adhesive composition of the present invention may contain a polyol other than the above polyester polyol (ABCD) in the adhesive. The polyol component is not particularly limited, and for example, polycarbonate polyol, polycaprolactone polyol, polyether polyol, polyolefin polyol, acrylic polyol, silicone polyol, castor oil-based polyol, fluorine-based polyol, etc. can be used.
[0069] <Optional ingredients> The adhesive of the present invention may further contain, as optional components, additives such as antioxidants, ultraviolet absorbers, hydrolysis inhibitors, antifungal agents, thickeners, plasticizers, pigments, and fillers, as necessary.
[0070] As the pigment, powder of either an inorganic compound or an organic compound can be used. The average particle size is 1×10 -4 mm or more and less than 0.2 mm, preferably 1×10 -3 mm or more 1×10-1 Powders having a size of less than 1 mm can be used.
[0071] Examples of inorganic compound powders include powders of aluminum oxide, aluminum silicate, aluminum hydroxide, alumina white, potassium sulfate, zinc oxide, zinc carbonate, magnesium aluminometasilicate, magnesium silicate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, barium sulfate, barium carbonate, calcium carbonate, calcium hydroxide, calcium oxide, calcium silicate, calcium sulfite, calcium sulfate, titanium oxide, silica, zeolite, activated carbon, kaolin, talc, rosewood clay, silica stone, mica, graphite, sericite, montmorillonite, sericite, sepiolite, bentonite, pearlite, zeolite, wollastonite, fluorite, dolomite, etc. Among these, silica and talc are used.
[0072] Examples of organic compound powders include powders of benzoguanamine resin, silicon resin, styrene resin, cross-linked polystyrene, epoxy resin, phenol resin, fluororesin, polyethylene resin, polyester resin, polyimide resin, polyamide resin, polyacetal resin, polyurethane resin, vinyl acetate copolymer resin, polyphenylene oxide resin, nylon 6, nylon 12, cellulose, acrylic resin, methacrylic resin, etc. Among these, benzoguanamine resin is used.
[0073] By including a pigment in the adhesive of the present invention, excellent coating appearance and good adhesive performance can be obtained. The adhesive containing the powder of the pigment component exhibits thixotropic flow properties, and when subjected to strong shearing forces on the coating roll during coating, it becomes low-viscosity and is transferred from the roll to the substrate. The adhesive composition transferred to the substrate rapidly exerts structural viscosity, quickly fixes to the substrate, and a good appearance can be obtained.
[0074] In the present invention, the pigment content is appropriately selected depending on the required performance, adhesion method, etc., but is preferably 0.01 to 10 mass % based on the total amount of adhesive.
[0075] The pigment component may be blended into the polyester component, into the polyisocyanate compound, into both the polyester and the polyisocyanate compound, or even into the polyester and the polyisocyanate compound when they are mixed. In order to further improve the adhesive performance, it is possible to use an adhesive assistant such as a silane coupling agent, phosphoric acid, a phosphoric acid derivative, an acid anhydride, a tacky resin, etc. In addition, it is possible to use a known catalyst, additive, etc. in order to adjust the curing reaction.
[0076] <Laminate> The laminate of the present invention (hereinafter also referred to as "composite film") comprises a sheet-like substrate and an adhesive layer formed from an adhesive containing the polyester or polyurethane polyester of the present invention. In the composite film of the present invention, the adhesive exhibits biodegradability under specific conditions, and the adhesive layer can be decomposed. The configuration of the laminate of the present invention is not particularly limited, but it is preferable that not only the adhesive layer but also some or all of the base materials constituting the laminate are biodegradable. Since the adhesive layer or the laminate itself of the present invention is biodegradable, it can be suitably used for consumer goods such as food packaging pouches, refill pouches for detergents, medicines, etc.
[0077] <Sheet-shaped substrate> Examples of sheet-like substrates include gas barrier substrates such as plastic films, papers and metal foils, which are generally used in packaging laminates, as well as sealants. Examples of plastic films include polyester resin films such as polyethylene terephthalate, polyethylene naphthalate (PEN), polylactic acid (PLA), and polybutylene succinate (PBS); polyolefin resin films such as polyethylene (PE) and polypropylene (PP); polystyrene resin films; polyamide resin films such as nylon 6 and poly-p-xylylene adipamide (MXD6 nylon); polycarbonate resin films; polyacrylonitrile resin films; cellulose films; polyimide resin films; laminates thereof (e.g., nylon 6 / MXD6 / nylon 6, nylon 6 / ethylene-vinyl alcohol copolymer / nylon 6), and mixtures thereof. Among these, those having mechanical strength and dimensional stability are preferred. The paper includes natural paper and synthetic paper. As the gas barrier substrate, aluminum foil and plastic films having a vapor-deposited layer of aluminum, silica, alumina, etc. are preferable. For example, in the case of aluminum foil, a thickness in the range of 3 to 50 μm is preferable from an economical point of view.
[0078] Examples of the sealant include polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and high-density polyethylene (HDPE), acid-modified polyethylene, polypropylene (PP), acid-modified polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-(meth)acrylic acid copolymer, polyolefin resins such as ionomers, etc. Among them, polypropylene-based resins are preferred from the viewpoint of heat resistance during retort, and unstretched polypropylene is particularly preferred from the viewpoint of heat-sealing properties. The thickness of the sealant is not particularly limited, but is preferably in the range of 10 to 60 μm, more preferably 15 to 40 μm, taking into consideration processability into packaging materials, heat sealing properties, etc. Also, by providing the sealant with unevenness with a height difference of 5 to 20 μm, it is possible to impart slipperiness and tearability of packaging materials to the sealant. The method for laminating the sealant is not particularly limited, and examples thereof include a method of laminating an adhesive layer and a sealant film by heat (thermal lamination, dry lamination) described below, and a method of melting a sealant resin, extruding it onto the adhesive layer, and cooling and solidifying it to laminate (extrusion lamination method). In order to biodegrade the laminate of the present invention, the sheet-like substrate is preferably biodegradable, and particularly preferred are polylactic acid, polybutylene succinate, cellophane and paper.
[0079] <Layer structure> The configuration of the laminate is not particularly limited, but it is preferable that the laminate has an adhesive layer on the outermost layer of one or more layers of sheet-like substrate, or that the laminate has one or more layers of sheet-like substrate and a sealant laminated thereto. Specific laminate configurations include OPP / adhesive layer, PET / adhesive layer, paper / adhesive layer, PBS / adhesive layer, cellulose / adhesive layer, PLA / adhesive layer, PBS / adhesive layer / cellulose, PLA / adhesive layer / PBS, PBS / adhesive layer / aluminum-vapor-deposited cellulose, PBS / adhesive layer / paper, OPP / adhesive layer / CPP, OPP / adhesive layer / AL-vapor-deposited CPP, NY / adhesive layer / PE, NY / adhesive layer / CPP, PET / adhesive layer / NY / adhesive layer / CPP, transparent vapor-deposited PET / adhesive layer / NY / adhesive layer / CPP, PET / adhesive layer / AL / adhesive layer / CPP, PET / adhesive layer / AL / adhesive layer / PE, PET / adhesive layer / NY / adhesive layer / AL / adhesive layer / CPP, PET / adhesive layer / AL / adhesive layer / NY / adhesive layer / CPP, PBS / adhesive layer / cellulose, PBS / adhesive layer / aluminum-vapor-deposited cellulose, PBS / adhesive layer / paper, and the like. These laminates may have a printed layer, a top coat layer, or the like, as necessary. In order for the laminate of the present invention to have biodegradability, the sheet-like substrate is also preferably a biodegradable substrate, particularly preferably paper / adhesive layer, PBS / adhesive layer, cellulose / adhesive layer, PLA / adhesive layer, PBS / adhesive layer / cellulose, PLA / adhesive layer / PBS, PBS / adhesive layer / aluminum-deposited cellulose, or PBS / adhesive layer / paper.
[0080] In addition, OPP is biaxially oriented polypropylene, PET is polyethylene terephthalate, PBS is polybutylene succinate, CPP is non-oriented polypropylene, NY is nylon, PE is polyethylene, AL is aluminum, and PLA is polylactic acid.
[0081] <Adhesive layer> The adhesive layer is a layer formed from the adhesive of the present invention, and the adhesive layer can be formed by, for example, applying the adhesive onto a sheet-like substrate. Furthermore, when sheet-like substrates are laminated using the adhesive of the present invention to form a laminate, the adhesive can generally be applied to one side of a first sheet-like substrate, and after a drying process as necessary, the laminate can be formed by bonding it to one side of a second sheet-like substrate.
[0082] The amount of adhesive layer is optional, but should be 0.1 to 6 g / m2 relative to the area of the adhesive surface. 2 The range of 0.5 to 4 g / m2 after drying is preferable. 2 In the adhesive of the present invention, since the polyester or polyester polyurethane is biodegradable, the adhesive layer remains biodegradable even after reaction with the crosslinking agent that is optionally contained. EXAMPLES
[0083] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. In the synthesis examples and examples, the number of parts of materials is calculated based on the non-volatile content, excluding the solvent, and blank spaces indicate that the material is not blended. In the following examples and comparative examples, "parts" and "%" respectively represent "parts by mass" and "% by mass" unless otherwise specified.
[0084] The glass transition temperature, number average molecular weight, acid value, hydroxyl value, and viscosity at 60° C. were measured by the following methods. <Glass transition temperature> The glass transition temperature (Tg) was measured by DSC (differential scanning calorimetry). Specifically, about 2 mg of polyester (PES-1) was weighed on an aluminum pan, the aluminum pan was set in a DSC measurement holder, and the endothermic peak of the chart obtained under the temperature increase condition of 5°C / min was read. The peak temperature at this time was taken as the glass transition temperature.
[0085] <Measurement of number average molecular weight> The number average molecular weight was determined using a Tosoh GPC (gel permeation chromatography) "HPL-8420GPC" and calculated as a standard polystyrene equivalent value. Tetrahydrofuran was used as the measurement solvent for GPC. The measurement sample was diluted with tetrahydrofuran so that the sample concentration was 0.5% to 1%, and a sample for GPC molecular weight measurement was prepared. Model: TOSOH HLC-8420GPC Column: TSKGEL SuperHZM-N Solvent: THF solution, Flow rate: 0.35 ml per minute, Temperature: 40° C. Detector: Differential refractometer Molecular weight standard: Polystyrene equivalent
[0086] <Acid value measurement> Approximately 1g of sample (polyester polyol solution) was precisely weighed and placed in a stoppered Erlenmeyer flask, and dissolved in 100ml of toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1), and phenolphthalein test solution was added as an indicator and held for 30 seconds.Then, titration was performed with 0.1N alcoholic potassium hydroxide solution until the solution turned a light pink color, and the acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S S: Amount of sample collected (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) F: Factor of 0.1N alcoholic potassium hydroxide solution
[0087] <Hydroxyl value> The hydroxyl value was measured according to the test method of JIS K-0070.
[0088] <Viscosity measurement at 60℃> The viscosity at 60° C. was measured using a cone plate viscometer (CV-S1, manufactured by Toa Kogyo Co., Ltd.) under the following conditions. Temperature: 60℃ Sample volume: 0.2 ml Rotor No.: 20P cone Rotor speed: 188 rpm Rotation time: 30 seconds
[0089] <Production of Polyester Polyol (AB)> [Polyester polyol (Synthesis example 1: AB-1)] 83.7g (1.1mol) of 1,2-propylene glycol derived from a plant having a branched structure as diol (a) having a branched structure, and 118g (1.0mol) of succinic acid derived from a plant having an aliphatic dicarboxylic acid as aliphatic dicarboxylic acid having 2 to 12 carbon atoms as aliphatic dicarboxylic acid (b) were placed in a reaction vessel, gradually heated to 160 to 240°C while stirring under a nitrogen stream, and esterification reaction was carried out at 240°C until the acid value became 15 or less, and then gradually reduced pressure to 1 to 2 torr, and excess hydroxyl group components were distilled off to obtain polyester (AB-1). Assuming that excess hydroxyl group components were distilled off almost evenly, and the total of carboxylic acid components and hydroxyl group components was 200 mol%, the composition of the obtained polyester polyol (AB-1) was succinic acid: 1,2-propylene glycol = 100: 100 (mol%). The resulting polyester polyol (AB-1) had a number average molecular weight of 1009, a hydroxyl value of 111.2 mgKOH / g, an acid value of 0.5 mgKOH / g and a viscosity at 60°C of 1,600 mPa·s.
[0090] [Polyester polyols (Synthetic examples 2 to 18: AB-2 to AB-18)] Polyester polyols (AB-2 to AB-18) were obtained in the same manner as in Synthesis Example 1, except that the diol component and dicarboxylic acid component and their compositions were changed as shown in Tables 1 and 2. However, AB-2 to AB-15 are polyester polyols (AB), and AB-16 to AB-18 are polyester polyols other than polyester polyols (AB). The acid value, hydroxyl value, number average molecular weight, and viscosity at 60° C. of each compound are shown in Table 1.
[0091] [Table 1]
[0092] The abbreviations in Table 1 are as follows. <Diol with branched structure (a)> a-1; 1,2-propylene glycol a-2; Neopentyl glycol a-3; 2-Butyl-2-ethyl-1,3-propanediol a-4; 3-Methyl-1,5-pentanediol a-5: Dimer diol obtained by reducing cyclic and acyclic dimer acids (mainly C=36) obtained by dimerizing natural higher unsaturated fatty acids: (Kuroda: Pripol 2033) <Other hydroxyl group components> a'-1; Ethylene glycol a'-2; 1,3-propylene glycol a'-3;1,4-butanediol a'-4;1,6-Hexanediol a'-5; Trimethylolpropane
[0093] [Example 1] <Polyester polyol (ABCD-1)> In order to obtain the desired number average molecular weight of 3,000, 33.3 g of polyester polyol (AB-1), 46.7 g of meso-lactide made of plant-derived components as lactide (C), 20.0 g of ε-caprolactone as cyclic monomer (D), and 0.02 g of tin 2-ethylhexanoate as a catalyst were placed in a reaction vessel, and the mixture was heated to 170°C while stirring under a nitrogen stream to cause a reaction. After 5 hours from the reaction, the pressure was gradually reduced to 1 to 2 torr, and the unreacted lactide (C) and cyclic monomer (D) were distilled off to obtain polyester polyol (ABCD-1). The obtained polyester polyol (ABCD-1) had a number average molecular weight of 3,000, a hydroxyl value of 37.5 mgKOH / g, a glass transition temperature of -28°C, and a viscosity at 60°C of 7,800 mPa·s.
[0094] [Examples 2 to 25, Comparative Examples 1 to 5] Polymerization was carried out so as to obtain the compositions and molar ratios of polyester polyols (AB-2 to AB-18), lactide (C), and cyclic monomer (D) as shown in Tables 2 and 3, to obtain polyester polyols (ABCD-2 to ABCD-25, PES-1 to PES-5).
[0095] [Table 2]
[0096] [Table 3]
[0097] [Example 31] <Adhesive composition> Next, 100 parts of the obtained polyester polyol (ABCD-1) was charged into a reaction vessel, and 15 parts of Toyo Morton's TSN-4864B-3 (aliphatic / polyether crosslinking agent: NCO terminal) was added as a crosslinking agent while stirring to obtain an adhesive composition.
[0098] [Examples 32 to 55, Comparative Examples 6 to 12] As shown in Tables 4 and 5, adhesive compositions were obtained using the obtained polyester polyols in the same manner as in Example 31. As the lactide (C), meso-lactide, L-lactide, D-lactide, and glycolide, which are plant-derived components, were used.
[0099] The abbreviations in Tables 4 and 5 are as follows. <Crosslinking agent> TSN-4864B-3: (Toyo Morton aliphatic / polyether crosslinking agent: NCO terminal) EA-N373A: (Toyo Morton aromatic / polyether crosslinking agent: NCO terminal) EA-N373B: (Toyo Morton aromatic / polyether crosslinking agent: OH end)
[0100] [Table 4]
[0101] [Table 5]
[0102] [Example 56] <Polyester polyurethane having isocyanate group (X-1)> 100g of polyester polyol (ABCD-1: hydroxyl value 37.5mgKOH / g) and 10.3g of 1,5-pentamethylene diisocyanate (NCO%: 25%) were charged into a reaction vessel and heated at 100-120℃ for 50 minutes while stirring under a nitrogen gas flow to obtain polyester polyurethane (X-1) having isocyanate groups. The obtained polyester polyurethane (X-1) having isocyanate groups had a number average molecular weight of 3,500, a glass transition temperature of -20℃, and a viscosity of 8,000mPa·s at 60℃.
[0103] [Example 58] <Adhesive composition> Next, 100 parts of the polyester polyol ABCD-10 of the present invention was charged into a reactor, and 10 parts of the polyester polyurethane (X-1) having an isocyanate group was added as a crosslinking agent with stirring to obtain an adhesive composition.
[0104] [Examples 57 and 59] Polyester polyol (ABCD-1) and 1,5-pentamethylene diisocyanate were polymerized to obtain polyester polyurethane (X-2) having isocyanate groups, as shown in Table 6. The obtained polyester polyurethane (X-2) having isocyanate groups had a number average molecular weight of 13,000, a glass transition temperature of -10°C, and a viscosity at 60°C of 20,000 mPa s. Subsequently, as shown in Table 7, the obtained polyester polyurethane (X-2) having an isocyanate group was used to obtain an adhesive.
[0105] [Table 6]
[0106] [Table 7]
[0107] <Adhesive evaluation> The resulting adhesive composition was evaluated for biodegradability and the biomass ratio was calculated. Furthermore, a laminate (composite film) was produced using the resulting adhesive composition by the following method. When the viscosity of the biodegradable polyester or biodegradable polyester polyurethane at 60°C was 5,000 mPa·s or more, a laminate was produced using an adhesive composition diluted with ethyl acetate in order to improve the leveling properties. The adhesive strength of the obtained laminate was evaluated as follows, and the results are shown in Tables 4, 5, and 7.
[0108] <Evaluation of biodegradability> The adhesive compositions shown in Tables 4, 5, and 7 were evaluated for biodegradability in accordance with JIS K 6953-1. 5: Biodegradation percentage 80% or more 4: Biodegradability percentage: 60% to less than 80% 3: Biodegradability percentage: 40% to less than 60% 2: Biodegradability percentage: 20% to less than 40% 1: Biodegradability percentage less than 20%
[0109] <Biomass ratio (plant-derived components)> For the adhesive compositions shown in Tables 3 and 5, the plant-derived component contents (mass %) were calculated.
[0110] (Preparation of composite film (laminate)) The adhesive composition was applied to the surface of a polybutylene succinate (PBS) film (Mitsubishi Chemical FZ91PM: substrate thickness 30 μm) using a test coater (application amount: 3.0 g / m 2 ), and cellophane (Mftamura Chemical Co., Ltd.: MST G-8, base material thickness 23 μm) was laminated on the coated surface. When the adhesive was diluted with a solvent, the coating amount after the solvent dried was 3.0 g / m 2 The adhesive was applied so that These laminates were placed in a thermostatic chamber at 40°C and left to stand for 3 days to produce composite films (laminates). Each composite film was produced in the same manner except for changing the substrate used. The adhesive strength of each of the obtained composite films (laminates) was measured as described below, and the results are shown in Tables 3 and 5. Polybutylene succinate (PBS) film: Mitsubishi Chemical FZ91PM substrate, thickness 30 μm Cellulose film: Futamura Chemical Co., Ltd.: MST G-8 substrate thickness 23 μm Biaxially oriented polypropylene (OPP) film: Toyobo P2161, substrate thickness 20 μm Non-oriented polypropylene (CPP) film: FHK2 made by Futamura Chemical Co., Ltd., substrate thickness 25 μm Biodegradable film: Futamura Chemical Co., Ltd. Aluminum-deposited NatureFlex 23NM Paper: Nippon Paper Industries Co., Ltd. Capital Wrap, semi-gloss kraft paper (bleached), 100g / m 2
[0111] (Adhesive strength) The composite film (laminate) was cut into a length of 300 mm and a width of 15 mm to prepare a test piece. Using an Instron tensile tester, the film was pulled at a peel rate of 300 mm / min to measure the T-peel strength (N / 15 mm) between various substrates. This test was carried out five times, and the average value was calculated and evaluated according to the following criteria. An adhesive strength of 2 or more is acceptable for practical use, and the higher the standard value, the better the result. 4: 2.5N / 15mm or more - Base material breaks 3: 1.7N / 15mm or more - 2.5N / 15mm or less 2: 1.0N / 15mm or more - 1.7N / 15mm or less 1: Less than 1.0N / 15mm
Claims
1. A polyester polyol which is a polymer of a polyester polyol (AB) having a number average molecular weight of 300 to 3,000, a lactide (C), and a cyclic monomer (D) (excluding lactide (C)), The polyester polyol (AB) is a reaction product of a hydroxyl group component (A) containing a diol (a) having a branched structure and a carboxylic acid component (B) containing an aliphatic dicarboxylic acid having 2 to 12 carbon atoms (b), The diol (a) having a branched structure includes one selected from the group consisting of 1,2-propylene glycol, 3-methyl-1,5-pentanediol, neopentyl glycol, 2-butyl-2-ethyl-1,3-propanediol, 1,3-butanediol, 2,4-diethyl-1,5-pentanediol, and 2-ethyl-1,3-hexanediol. Polyester polyol.
2. 2. The polyester polyol according to claim 1, wherein the cyclic monomer (D) comprises ε-caprolactone.
3. 3. The polyester polyol according to claim 1, wherein the content of the diol component (a) having a branched structure is 15 to 100 mol % in 100 mol % of the hydroxyl group component (A).
4. The polyester polyol according to any one of claims 1 to 3, wherein the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms comprises at least one member selected from the group consisting of succinic acid, sebacic acid, and azelaic acid.
5. The polyester polyol according to any one of claims 1 to 4, wherein the content of the aliphatic dicarboxylic acid (b) having 2 to 12 carbon atoms is 30 to 100 mol % in 100 mol % of the carboxylic acid component (B).
6. A polyester polyurethane (X) having an isocyanate group, which is a reaction product of the polyester polyol according to any one of claims 1 to 5 and a polyisocyanate (E).
7. An adhesive comprising the polyester polyol according to any one of claims 1 to 5.
8. An adhesive comprising the polyester polyurethane (X) having an isocyanate group according to claim 6.
9. A laminate comprising an adhesive layer formed from the adhesive according to claim 7 or 8 on a sheet-like substrate.
10. 10. The laminate according to claim 9, wherein the sheet-like substrate is biodegradable.
Citation Information
Patent Citations
Method for producing polyester polyol and curable resin composition
JP1993262869A
Production of lactic acid copolyester and packaging material
JP1995173266A
Polyurethane resin
JP1996067733A
Lactic acid based polyester laminate paper
JP1996300570A
Biodegradable polyester
JP2003048964A